2014
DOI: 10.1051/swsc/2014033
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of upper atmospheric emissions calculations to solar/stellar UV flux

Abstract: The solar UV (UltraViolet) flux, especially the EUV (Extreme UltraViolet) and FUV (Far UltraViolet) components, is one of the main energetic inputs for planetary upper atmospheres. It drives various processes such as ionization, or dissociation which give rise to upper atmospheric emissions, especially in the UV and visible. These emissions are one of the main ways to investigate the upper atmospheres of planets. However, the uncertainties in the flux measurement or modeling can lead to biased estimates of fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
(74 reference statements)
0
7
0
Order By: Relevance
“…Fig. 1 from Barthelemy & Cessateur 2014). Both TSI and SSI measurements are of primary interest for space weather and space climate studies.…”
Section: Introductionmentioning
confidence: 99%
“…Fig. 1 from Barthelemy & Cessateur 2014). Both TSI and SSI measurements are of primary interest for space weather and space climate studies.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of an accurate knowledge of the solar UV flux and its variability for space weather purposes has been previously debated (Lilensten et al 2008;Barthelemy & Cessateur 2014). On the basis of several examples, we will show how important an accurate knowledge of solar UV fluxes in terms of dayglow emission modeling is, especially during solar eruptive events.…”
Section: Discussion About the Solar Uv Fluxmentioning
confidence: 93%
“…In a more general space weather frame, the second motivation is following Barthelemy & Cessateur (2014) studies on the solar UV flux accuracy to demonstrate on a case study, i.e. Europa and Ganymede, how the knowledge of the solar UV flux is of primary importance regarding the visible red and green dayglow emission estimations especially in the case of solar eruptive events.…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…They found that for the spectrum of November 2011, when an auroral spot was positively detected, a small contribution of H 2 emission was identified providing, hence, evidence for the presence of precipitating electrons, giving a total energy input of at least 150 GW. In the context of space weather, it is important to note that Barthelemy et al (2014) did not find any evidence for auroral electron-induced emission above the detection threshold in any other spectra except for those corresponding to November 2011. Future in-situ plasma and energetic neutral particle observations could provide significant feedback for the determination of the planet's space weather conditions and for determining if they indeed have a key role in this context.…”
Section: Space Weather In the Outer Solar Systemmentioning
confidence: 84%
“…It is underlined that one of the major open questions regarding Uranus is the determination of the exact mechanism providing the required additional heating of the planet's upper atmosphere. In a recent study, Barthelemy et al (2014) analysed HST FUV spectral images obtained in November 2011 (Lamy et al 2012) and in 2012, with the scope to extract any possible H 2 emission produced in the upper atmosphere of the planet. For their interpretations of the data, they used simulated H 2 emissions created by energetic particle precipitation in the upper atmosphere.…”
Section: Space Weather In the Outer Solar Systemmentioning
confidence: 99%